Composition, abundance and distribution of epiphytes on seagrasses in Carles, Iloilo, West Central Philippines - Ilanga, Mary Christine S.
Seagrass meadows provide excellent substratum for epibenthic organism to cling or live on. This study aims to identify, determine and compare the species composition of epiphytes in three seagrass sites in Carles, Iloilo, namely: Daculan, Bancal, and Cabilao Grande from surveys conducted in October 2014. Essentially, this study provides baseline information on the epiphytic organisms present in the three sites in Carles, Iloilo and allows opportunities for further investigation of the significance of epiphytic organisms to the productivity of the said coastal area. The results showed differences in mean density between the three sites; Bancal being the densest, while Daculan, as the least dense. One-way ANOVA showed a significant difference (F=29.26, P<0.05) in density with location within the grassbed. A total of 52 taxa were identified in three sites. The most abundant taxon in all sites in Order Foraminifera, which also comprised around 60-80% of the epiphytes in three stations. The top five most abundant taxa in Bancal and in Cabilao Grande were Forams, Cyclopoids, Syllidae, Nematodes and Sabellidae. However, in Daculan, Bivalves and Gastropods replaced Sabellidae and Cyclopoids in the five most abundant taxa found in the three stations. Moreover, epiphyte density did not show any significant correlation with any abiotic factor, as reflected in this study.